2015
DOI: 10.1186/s13017-015-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal hypertension; prevalence, incidence and outcomes in a low resource setting; a prospective observational study

Abstract: BackgroundIntra-abdominal hypertension (IAH) is defined as a sustained elevation in intra-abdominal pressure (IAP) greater than or equal to 12 mmHg. IAH has been shown to cause organ derangements and dysfunction in the body. Objective screening of IAH is neither done early enough nor at all thus leading to significant morbidity and mortality among surgical patients. The epidemiology and outcome of IAH among surgical patients has not been documented in Uganda. The aim of this study was to determine the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…A prospective cohort study of 38 critically ill postlaparotomy patients in Zimbabwe, found prevalence of IAH of 92% and ACS at 8% [11]. Another prospective study, involving 192 paediatric and adult patients in general surgical wards in Uganda, reported IAH prevalence of 25 and 18.4% for paediatric and adult population, respectively [12]. …”
Section: Introductionmentioning
confidence: 99%
“…A prospective cohort study of 38 critically ill postlaparotomy patients in Zimbabwe, found prevalence of IAH of 92% and ACS at 8% [11]. Another prospective study, involving 192 paediatric and adult patients in general surgical wards in Uganda, reported IAH prevalence of 25 and 18.4% for paediatric and adult population, respectively [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In order to succeed in this great challenge it is important to understand the pathophysiology of abdominal hypertension 25 and spread the new knowledge among physicians and surgeons working in lowincome hospitals. 26 Even in case of scarce resources, the concept of damage control surgery and its application with tension-free closure of the abdominal wall after abbreviated laparotomies can increase survival rates in critical patients. 27 Moreover the awareness of the potential complications for clinicians and staff using laparostomy should be mandatory not to turn a good surgical tool into malpractice.…”
Section: Discussionmentioning
confidence: 99%
“…Each IAP value was obtained by manometer (cmH2O) and recalculated in millimeter mercury using the conversion factor (1 cmH2O = 0.74 mmHg). The measuring system is closed and the urinary drainage bag clamp released at the end of the procedure (Kuteesa et al, 2015).…”
Section: Fig (1)mentioning
confidence: 99%